Oral health promotion evaluation – time for development - Watt RG, Fuller S, Harnett R, Treasure ET, Stillman-Lowe C (Blackwell Synergy, 2001)
Increasing emphasis is now being placed upon the evaluation of health service interventions to demonstrate their effects. A series of effectiveness reviews of the oral health education and promotion literature has demonstrated that many of these interventions are poorly and inadequately evaluated.